EMPLOYEE PERFORMANCE IMPROVEMENT THROUGH DREAM (Digital Room For E-Learning Modules) APPLICATION TRAINING BASED ON E-LEARNING AT BANK BTN CIMAHI BRANCH - Silaen, Sangkut Harpend Yohanes; Afrilianto, Muhammad; Noor, Agus Hasbi (IKIP Siliwangi Bandung, 2021)
The purpose of this research is to study the performance of employees of Bank BTN Cimahi Branch through DREAM application training based on e-learning. This study is quantitative research. The type of data used in this study is quantitative data with data sources are primary data and secondary data. Methods of data collection using the registration document. Location Research was conducted at Bank BTN Branch Cimahi with the selection of a random sample of 3 different units as many as 30 people employees. Data were analyzed using inferential statistics, with test One sample t-test (one group) with SPSS version 22.0. Based on the results of data analysis obtained Sig. (2-tailed) N-Gain = 0.00 < Î± = 0.05. This shows that there is an increase in the performance of employees of Bank BTN Cimahi Branch through DREAM application training based on e-learning.Â